A Case Study: Optimizing CDS for Pediatric Oncology Trials by Transitioning from Interruptive to Passive Alerts - Potashner, Renee; Meyer, Natalie; Patterson, Erica; Jessa, Karim; Yan, Adam Paul (Applied Clinical Informatics, 2025)
Many children with cancer are treated as part of interventional clinical trials. Ensuring that the correct chemotherapy treatment plan is used is paramount.The objectives of this report were to: (1) highlight the initial design of a clinical decision support (CDS) tool that was intended to help ensure the correct matching of research studies to research chemotherapy medications, (2) discuss the issues identified with the CDS tool, and (3) review the redesign of the tool that was done to overcome the issues identified.We previously utilized an interruptive alert developed by Epic Systems to identify mismatches between a patient's chemotherapy plan and research study. We identified an issue with the logic of the alert resulting in the alert firing inappropriately.We estimate that the chemotherapy-research plan alert fired when 93.4% of treatment plans were applied (17.3 alerts/provider/year). A high number of misfiring alerts were identified due to the inclusion of our institution name as both (1) a “tag” in the research protocol, and (2) an unallowed tag in the research study record. Since the tag was included in all protocols, but also unallowed in all research records the alert fired with the application of almost all treatment plans. We developed a new mechanism to provide CDS that did not involve an interruptive alert. Within the research study record, we manually associate compatible treatment plans to that study record, and then when an oncologist goes to order chemotherapy the system prioritizes the display of compatible treatment plans to the oncologist. The goal of the redesigned CDS approach is to eliminate interruptive alerts while ensuring the correct chemotherapy plan is selected.With end-user engagement and creative approaches to CDS design, interruptive alerts can be transitioned into passive and effective CDS tools.
Keywords: pediatrics; chemotherapy; clinical decision support; oncology; clinical trial